Volumetric brain correlates of gait associated with cognitive decline in community-dwelling older adults - Victoria N. Poole; Victoria N. Poole; Shahram Oveisgharan; Shahram Oveisgharan; Lei Yu; Lei Yu; Robert J. Dawe; Robert J. Dawe; Sue E. Leurgans; Sue E. Leurgans; Sue E. Leurgans; Shengwei Zhang; et al. (Frontiers in Aging Neuroscience, 2023)
ObjectiveTo determine the extent to which the regional brain volumes associated with slow gait speed can inform subsequent cognitive decline in older adults from the Rush Memory and Aging Project.ApproachWe utilized deformation-based morphometry (DBM) in a whole-brain exploratory approach to identify the regional brain volumes associated with gait speed assessed over a short distance during an in-home assessment. We created deformation scores to summarize the gait-associated regions and entered the scores into a series of longitudinal mixed effects models to determine the extent to which deformation predicted change in cognition over time, controlling for associations between gait and cognition.ResultsIn 438 older adults (81 ± 7; 76% female), DBM revealed that slower gait speed was associated with smaller volumes across frontal white matter, temporal grey matter, and subcortical areas and larger volumes in the ventricles during the same testing cycle. When a subset was followed over multiple (5 ± 2) years, slower gait speed was also associated with annual declines in global cognition, executive functioning, and memory abilities. Several of the gait-related brain structures were associated with these declines in cognition; however, larger ventricles and smaller medial temporal lobe volumes proved most robust and attenuated the association between slow gait and cognitive decline.ConclusionRegional brain volumes in the ventricles and temporal lobe associated with both slow gait speed and faster cognitive decline have potential to improve risk stratification for cognitive decline in older adults.